PENDAMPINGAN LITERASI KRITIS NATION DAN CHARACTER BUILDING PESERTA MAGANG TEKNOLOGI ANIMASI DI NUSANTARA CULTURE ACADEMY (NCA) MALANG TAHUN 2021 - Umi Salamah; Rokhyanto Rokhyanto; Kingkin Puput Kinanti (JPM PAMBUDI, 2021)
The writing of this article is based on the results of serving the community which aims to strengthen the sense of love for the Indonesian nation and state so that the Millennial generation can dedicate their mastery of science and technology to the progress and welfare of the nation. By practicing critical literacy, it is hoped that participants will have strong filters and principles in receiving information on social media, so they are not easily provoked by hoax news. The target of the service is animation technology apprentices at NCA Malang batch 2. Pattern means to make a model the spirit of nationalism and the courage of the freedom fighters and millennial fighters; discuss means the intention to choose a form of struggle that is suitable for the participants in the millennial era, and implement means the intention to carry out in everyday life. The mentoring technique is done by playing games, screening of documentaries and film millennial choices, singing and living the national anthem, presenting and solving problems. To avoid the spread of Covid 19 during the pandemic, teh mentoring is carried out virtually. The results obtained are (1) the occurrence of understanding how to implement nation and character building in real life; (2) can contribute positively to the community, and (3) have the confidence to be able to develop talents to elevate local potential into phenomenal works.